Effect of Music Therapy in Reduce the Level of Depression in the Elderly: Literature Review - Rahmawati, Primasari Mahardhika; S, Suhari; Tri Noval Refansya, Rizki (Universitas Bondowoso, 2022)
Introduction: Depression is the most common in the elderly who commit suicide as much as 15% and is one of the diseases that are often found in the elderly that can cause emotional disturbances related to psychology. Music therapy is an important and easy intervention for depressed elderly to reduce depression levels. Music therapy is a therapy to relax the mind. The purpose of this review is to determine the effect of music therapy in reducing depression in the elderly. Method: The method used in preparing the Literature Review uses PICOS. Secondary data obtained from journals with a predetermined discussion. Results Based on literature search through three databases. Researchers get 1,535 articles that match the keywords. then filtered by title, abstract, and text (n=10) which were adjusted to the inclusion criteria. Result: There are 10 journals found, this literature generally recommends giving music therapy to the elderly who are depressed by paying attention to music criteria, features and safety in giving therapy so that it can increase the improvement of therapy. Conclusion:Music therapy has an effect on alpha waves which will stimulate the release of the neurotransmitter serotonin. Serotonin hormone can cause feelings of happiness, because it is a neurotransmitter that affects feelings. Furthermore, serotonin will be converted into the hormone melatonin which has a relaxing effect and mood changes so that it can reduce depression levels.